A further examination of the export-led growth hypothesis - Dierk Herzer (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2010)
This paper challenges the common view that exports generally contribute more to GDP growth than a mere change in export volume, as the export-led growth hypothesis predicts. Applying heterogeneous panel cointegration techniques to a production function model with non-export GDP as the dependent variable, we find for a sample of 45 developing countries that: (i) exports have a positive short-run effect on non-export GDP in developing countries, (ii) the long-run effect of exports on non-export output, however, is negative on average, and (iii) there are large differences in the long-run effect of exports on non-export GDP across countries. Evidence from a simple regression analysis suggests that these cross-country differences in the long-run effect of exports on non-export GDP are significantly negatively related to cross-country differences in primary export dependence, business regulation, and labour regulation, whereas there is no statistically significant association between the growth effect of exports and the capacity of a country to absorb knowledge.
Keywords: F43; O11; C23; 330; Export-led growth; Developing countries; Panel cointegration; Exportinduziertes Wachstum; Nicht-handelbares Gut; Wirtschaftswachstum; Schätzung; Entwicklungsländer